Crossing the dotted line : cultural divides - Bevelander, Dianne; Nolan, Jacqueline; Page, Michael (Professor of management); Yue, Tao, active 2015 (London : Rotterdam School of Management, Erasmus University, 2015)
This case study is about the gender, cultural, and organizational issues that arise when Sema Isaura-Mans begins a new job as an account manager in a Dutch company. At first she enjoys the informal conversation between team members however, she soon becomes the butt of the joke due to short stature. After one meeting the matter comes to a head and Sema must decide how to proceed.
Originally Published In : Bevelander, D., Nolan, J., Page, M., & Yue, T. (2015). Crossing the Dotted Line: Cultural divides. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Work environment -- Case studies; Industrial sociology -- Case studies; Diversity in the workplace -- Case studies